The Ogham Inscriptions of Scotland and Brittonic Pictish. (1st January 2020) - Rodway, Simon
In this paper, I examine the evidence brought forward by Katherine Forsyth in support of the hypothesis that the 'Pictish' ogham inscriptions of Scotland are linguistically Celtic. Having examined the five most promising inscriptions minutely, I conclude that they are in fact not Celtic, and that 'Celtic-looking' sequences in them are due to coincidence. Thus, the language of this corpus of inscriptions remains unknown.